2015
DOI: 10.4314/ajid.v9i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Seronegative conversion of an HIV positive subject treated with <i>Nigella sativa</i> and honey

Abstract: Background: There are many documented roles of Nigella sativa and honey in treatment of diseases but the least expected are the potentials in curing HIV infection. Materials and Method: A 27 years old HIV infected woman was diagnosed during antenatal care (ANC) at General Hospital (EIA) and confirmed with Western blot in 2004 at National Institute of Medical Research, Lagos (NIMR). She could not benefit from free antiretroviral therapy because her CD4 count was above 200 cells/ µL (350 cells/ µL) thus herbal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…Similarly, a sustained seroreversion was noted in a 27-year-old HIV infected pregnant woman who was not eligible for antiretroviral therapy, received 10ml of N.sativa and honey mixture (60% of N.sativa seeds and 40% of honey) three times daily for a year. Repeated serology assessments for 10 years have shown undetectable viral load and CD4 count not less than 750 cells/μL [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a sustained seroreversion was noted in a 27-year-old HIV infected pregnant woman who was not eligible for antiretroviral therapy, received 10ml of N.sativa and honey mixture (60% of N.sativa seeds and 40% of honey) three times daily for a year. Repeated serology assessments for 10 years have shown undetectable viral load and CD4 count not less than 750 cells/μL [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, another study conducted by the same author on a sero-positive HIV infected woman revealed the efficacy of NS and honey therapy (10 mL thrice/day for 1 year) for sustained sero-reversion [92]. These effects can be ascribed to the probable virucidal activity of NS [91].…”
Section: Resultsmentioning
confidence: 99%
“…Onifade et al confirmed that treatment of a sero-positive human immunodeficiency virus (HIV) infected man with NS concoction (10 mL twice/day for six months) resulted in the reduction of the viral load to an undetectable level in 3 months, an elevation of the CD4 count, an alleviation of the symptoms, and a sustained sero-reversion [ 91 ]. Similarly, another study conducted by the same author on a sero-positive HIV infected woman revealed the efficacy of NS and honey therapy (10 mL thrice/day for 1 year) for sustained sero-reversion [ 92 ]. These effects can be ascribed to the probable virucidal activity of NS [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The repeat serology assessments for HIV infection became negative with undetectable viral load. The woman also got 3 children (2007, 2010, and 2012) that all were breastfed and none of the children infected with HIV and her repeat CD4 count was not less than 750 cells/ μ L [118]. Nowadays HIV/AIDS is a serious global threat and in this regard, N. sativa can be a promising natural therapy to cure such a chronic infectious disease, after validating its full therapeutic efficacy by further investigations.…”
Section: Pharmacological Activities Of Nigella Sativamentioning
confidence: 99%